Strategi Pengelolaan Sampah di Kawasan Wisata : Literatur Review - Marthin Y. J. Dethan; Ishak I. Muda; Wilibaldus K. Nahak; Luh Putu Ruliati (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Waste in tourist areas has become a complex environmental issue due to the increasing tourist activity that is not balanced with waste management capacity. This study aims to analyze various waste management strategies in tourist areas through a literature review approach. The research method follows the stages of Arksey & O'Malley (2005), which include identifying research questions, literature searches, article selection, data extraction, and synthesis of results. Literature sources came from the Google Scholar, ResearchGate, and Neliti databases, with the keywords "waste management" and "tourism area." Of the 50 articles found, 12 met the inclusion criteria for analysis. The review results indicate that waste management strategies in tourist areas generally lead to the implementation of the 3R principle (Reduce, Reuse, Recycle), increasing public and tourist awareness, multi-stakeholder collaboration, and strengthening local institutions such as waste banks and Pokdarwis. The main obstacles identified include low community participation, limited infrastructure, and a lack of technological support and sustainable policies. The conclusion of this study emphasizes that waste management in tourist areas must be participatory, sustainable, and integrated across sectors to support the creation of environmentally friendly tourist destinations.